INTEGRATION OF GOOGLE CLASSROOM INFERENCE STRATEGY AS BLENDED LEARNING MEDIA TOWARD ISLAMIC SENIOR HIGH SCHOOL STUDENTS' READING ABILITY - M. Arif Rahman Hakim; Echa Ananda Sari; Samsul Rizal; Yashori Revola; Ade Riska Nur Astari (AL LUGHAH, 2022)
The objective of this research is to investigate whether there is a significant effect of using Google Classroom as blended learning media integrated with inference strategy toward students’ reading ability. The design of this research was quasi experiment. In this design, two classes were used, experimental class and control class. The instrument on this research is reading test which aims to measure students’ reading comprehension.  The data in this research were analyzed by using SPSS v.20. It was to calculate the pre-test and post-test result. The finding of this research showed that there was a significant effect of using Google Classroom as blended learning media integrated with inference strategy toward students’ reading ability with the t-count of post-test = 5,518 > t-table with the sig. (2-tailed) = 0,000< 0,05 which means that H0 was rejected. It can be concluded that there was a significant effect of using Google Classroom as blended learning media integrated with inference strategy toward students’ reading ability to improve students’ reading ability at grade X of Senior High School in South Bengkulu-Indonesia.